2002
DOI: 10.1046/j.1365-2656.2002.00601.x
|View full text |Cite
|
Sign up to set email alerts
|

The population response to environmental noise: population size, variance and correlation in an experimental system

Abstract: summary  Variation in an organism’s environment can influence its life history and therefore its population size. Understanding the interplay between noise and population dynamics is of considerable importance, especially for prescribing management of economically important or threatened species. The impact of noise on population biology has been the subject of frequent theoretical investigations and discussed in posthoc analyses of time‐series. However, there is a dearth of experimental investigations.  Her… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
58
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(60 citation statements)
references
References 41 publications
2
58
0
Order By: Relevance
“…A similar experiment with Daphnia magna found that variation in food abundance increased the probability of extinction and decreased the time to extinction (Drake & Lodge 2004). Similarly, in two studies in the soil mite system described above, Benton et al (2001Benton et al ( , 2002 showed that increasing the variation in food supply increased population variation, so that populations fluctuated in synchrony with environmental variations. While no extinctions were observed in either of these studies, mean population size decreased with increasing environmental variation, with effect size depending on the life stage examined.…”
Section: Temporal Variationmentioning
confidence: 76%
See 1 more Smart Citation
“…A similar experiment with Daphnia magna found that variation in food abundance increased the probability of extinction and decreased the time to extinction (Drake & Lodge 2004). Similarly, in two studies in the soil mite system described above, Benton et al (2001Benton et al ( , 2002 showed that increasing the variation in food supply increased population variation, so that populations fluctuated in synchrony with environmental variations. While no extinctions were observed in either of these studies, mean population size decreased with increasing environmental variation, with effect size depending on the life stage examined.…”
Section: Temporal Variationmentioning
confidence: 76%
“…Increasing food variation should lead to greater probability of extinction and should decrease the time to extinction (Tuljapurkar & Orzack 1980;Davis et al 2003;Lande et al 2003). (Belovsky et al 1999;Benton et al 2001Benton et al , 2002Drake & Lodge 2004) (Grover 1988*;1991*) 11. Environmental stressor such as chemicals may decrease time to extinction.…”
Section: Introductionmentioning
confidence: 99%
“…Here we assume values of K to be gamma distributed, since this distribution is always positive and can easily be modified to have a range of different shapes. The gamma distribution can be used to describe the annual variation in cod abundance in the North Atlantic (Brynjarsdottir and Stefansson 2004;ICES Advice 2007), and also many other naturally occurring distributions, such as population and species abundance (Cadigan and Myers 2001;Benton et al 2002) and species diversity (McCain 2005;Cornell et al 2007). The gamma distribution is a continuous probability distribution (see the Poisson distribution for a discrete counterpart) governed by two parameters, a and b, which through the gamma function, f x ð Þ ¼ 1=CðaÞb a ð Þ x aÀ1 e Àx=b ; where 0\x\1; determine the expected value and the variance of the distribution.…”
Section: Variation In Carrying Capacitymentioning
confidence: 99%
“…Intrinsic factors include, for example, low or negative intrinsic growth rates and demographic stochasticity (Pimm et al 1988). Observations and experimental evidence suggest that, in real world conditions, population extinction may result from extrinsic factors such as habitat fragmentation (Gonzalez & Chaneton 2002), stochastic environmental variation (Benton et al 2002;Pike et al 2004), climate change (McCarty 2001) and overexploitation ( Fryxell et al 2005). In addition, invasive species may also be an important cause of population extinction (Clavero & García-Berthou 2005).…”
Section: Introductionmentioning
confidence: 99%